Squalamine and Its Aminosterol Derivatives: Overview of Biological Effects and Mechanisms of Action of Compounds with Multiple Therapeutic Applications - Nour Mammari; Elsa Salles; Audrey Beaussart; Sofiane El-Kirat-Chatel; Mihayl Varbanov (Microorganisms, 2022)
Squalamine is a natural aminosterol that has been discovered in the tissues of the dogfish shark (Squalus acanthias). Studies have previously demonstrated that this promoter compound and its derivatives exhibit potent bactericidal activity against Gram-negative, Gram-positive bacteria, and multidrug-resistant bacteria. The antibacterial activity of squalamine was found to correlate with that of other antibiotics, such as colistin and polymyxins. Still, in the field of microbiology, evidence has shown that squalamine and its derivatives have antifungal activity, antiprotozoa effect against a limited list of protozoa, and could exhibit antiviral activity against both RNA- and DNA-enveloped viruses. Furthermore, squalamine and its derivatives have been identified as being antiangiogenic compounds in the case of several types of cancers and induce a potential positive effect in the case of other diseases such as experimental retinopathy and Parkinson’s disease. Given the diverse effects of the squalamine and its derivatives, in this review we provide the different advances in our understanding of the various effects of these promising molecules and try to draw up a non-exhaustive list of the different mechanisms of actions of squalamine and its derivatives on the human organism and on different pathogens.